Significant Events Identified by Clients Engaged in Existential Psychotherapy: A Descriptive Phenomenological Exploration. (November 2020) - Sousa, Daniel; Vaz, Alexandre
This research focuses on the descriptions of significant events experienced in the context of existential psychotherapy as described by five clients. The results include a set of eidetic dimensions in which the human relationship stands out as being particularly meaningful. Clients considered the therapy process to be significant for a number of different reasons, ranging from the development of the capacity to cope with difficulties to a basic sense of increased self-understanding. Significant events in therapy are sometimes preceded by tensions between the therapist and the client, which, in turn, promote turning points and breakthroughs in the therapeutic relationship. The results also seem to corroborate the affect and interdependence of the relational dimensions of psychotherapy, such as common factors, and more specific ingredients, such as the techniques used by the therapist. However, the experience of significant events is multifaceted and dynamic, and only a holistic perspective would seem to do justice to the complexity of these interrelated phenomena. Implications for practice and research are discussed.